Analisis Pengaruh Customer Experience Terhadap Loyalitas Konsumen Di Sektor Jasa - Ni Dewi; Nyoman Amrita; Gede Pratama; Ni Setyawati (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of customer experience on consumer loyalty in the service sector. Customer experience is a crucial factor that reflects the overall interactions and perceptions of consumers toward the services they receive. This research uses a descriptive approach by reviewing literature and previous studies on the dimensions of customer experience, including sense, feel, think, act, and relate. The analysis indicates that customer experience significantly impacts loyalty through satisfaction, emotional attachment, and quality perception. The more positive the experience provided by a company, the more likely consumers are to repurchase, recommend the service, and remain loyal. Therefore, service companies must ensure consistent customer experience to maintain competitive advantage.